Is organum subfornicale of Rattus norvegicus a neuroendocrine gland ? A morphological study using histochemistry and immunohistochemistry methods. - Daryanto, Daryanto (Universitas Gadjah Mada, 1994)
The objective of this study is to provide evidence on whether the subfomical organ is a neuroendocrine gland, by which the neurosecretion process to be carried out in this organ. This investigation involved the use of light microscopy by using an immunohistochemistry as well as histochemistry methods and transmission electron microscopy. Eighty adult male and female albino rats of the Lembaga Makanan Rakyat strain (Jakarta) weighing between 150-250 g, and 9 rats of Wistar strain, weighing between 200-300 g, were studied.According to morphology and by using immunohistochemistry and histochemistry methods, the results revealed that the subfomical organ was not a neuroendocrine gland that secreted a neurohormone or neurosecretory substances through a neurosecretion process.Key Words: subfomical organ-neurosecretion process - transmission electron microscopy - inununohistochemistry technics - histochemistry technics.